THE STUDY OF THE PREFERRED SILHOUETTE FORMS OF CLOTHING MODELS FOR TYPICAL AND INDIVIDUAL FIGURES OF CONSUMERS - Mashhura Abduraimovna Abdukarimova; Soipova Zuhra Alisher qizi; Muhamadieva Indira Muxitdin qizi (Journals Park Publishing, 2022)
With the transition of modern society to new economic relations focused on the free market, there have been significant changes in the socio-economic conditions for the functioning of enterprises in the clothing industry and the attitude of consumers to the quality of manufactured products. During the period of saturation of the sales market with clothing, along with ensuring aesthetic and ergonomic indicators, requirements are placed on the possibility of forming a harmonious appearance by means of a suit.
Keywords: traditional design; model and its internal content; material structure